La interrogación en el purépecha de Carapan, Michoacán - Aranda Herrera, Alejandra (El Colegio de México, A.C., 2013)
This paper describes the form of interrogative clauses in Purepecha. It shows that interrogative mood markers take a different form depending on the preceding temporal or aspectual marker. Moreover, it presents new evidence showing that certain interrogatives can take “degraded” aspectual forms, which are characteristic of subordinate clauses.